Optimal Evaluation of the Rheological Parameters for STF Dampers in Semi-Rigid Joints of Steel Structures Using Response Surface Method - Ruby Freya; R. Senthil (Advances in Civil Engineering)
This work deals with the multiobjective optimization of rheolohical parameters on a novel designed flexible joints using shear thickening fluid dampers (STFD) on steel structures. The proposed damper consists of the shear thickening fluid (STF) with the combination of nano-silica and PEG (400) sonicated to achieve colloidal dispersion of nanoparticles. Series of cyclic loading were imposed on the frames equipped with STF dampers to assess their impacts on T-steel frames. The stiffener end plate is bolted over the corner of the joints that are subjected to bending moment. The multi-objective optimization using the response surface method of the rheological parameters for STF dampers was studied in order to reduce the dynamic forces and moments produced in a semi-rigid joint of the steel structures. Results from the analysis were used to obtain correlations between the response variables and the input factors (effective stiffness of 449.89 N/mm, complex viscosity of 98.69 Pa.s, and damping constant of 446.99 N.s/mm) for the proposed STF damped semi-rigid joints.